Studies on a Maize Mutant Sensitive to Low Temperature II. Chloroplast Structure, Development, and Physiology - Millerd, Adele (1969)
In the Zea mays L. mutant M11 grown in the dark at 15°, the ultrastructure of the etioplast is abnormal. The pigment content of the etioplasts is reduced but the in vivo absorption characteristics suggest that the normal protochlorophyll (ide)-holochrome is present. The lowered synthetic ability of the etioplasts is not primarily due to a reduced complement of plastid ribosomes. The plastids of mutant M11 grown in the light at 15° contain little pigment, are markedly deficient in ribosomes and their ultrastructure is abnormal. In mutant M11 grown at 15°, an extreme sensitivity of the plastid membranes to light was observed.